Intending to Leave But No Place to Go: An Examination of the Behaviors of Reluctant Stayers. Issue 2 (15th March 2019) - Sheridan, Sharon; Crossley, Craig; Vogel, Ryan M.; Mitchell, Marie S.; Bennett, Rebecca J.
ABSTRACT: We extend recent conceptual work on withdrawal states and develop a framework to examine behavioral tendencies of reluctant stayers (i.e., employees who desire to leave but cannot). Although principles of self-interest suggest that these employees ought to behave appropriately to maintain employment, reactance theory suggests that the combination of high turnover intentions and low job alternatives may result in lower performance and greater deviance. Contrary to conventional wisdom but consistent with reactance theory, low perceived job alternatives strengthened the positive relationship between turnover intentions and deviance, as well as the negative relation between intentions to quit and task performance. Moderated-mediation analyses revealed that the indirect effect of work frustration (via turnover intentions) was stronger on task performance and deviance when perceived job alternatives were low rather than high.